The association between low carbohydrate dietary score (LCDS) and cardiovascular risk factors: results from the Shiraz Heart Study (SHS) - Zahra Mosallanezhad; Mohammad Jalali; Cain C. T. Clark; Mohammad Javad Zibaeenezhad; Mehran Nouri; Seyyed Saeed Mohammadi; Mehrab Sayadi; Iman Razeghian-Jahromi; Nader Parsa; Fatemeh Zibaeenejad; Zahra Sohrabi (BMC Public Health, 2024)
Abstract Background Cardiovascular disease (CVD) is a major cause of death and recent studies have highlighted the potential role of dietary carbohydrate indices in cardiovascular health. Given the controversial results in this field, the aim of this study was to investigate the association between low carbohydrate dietary score (LCDS) and CVD risk factors in a population of Iranian adults. Methods This cross-sectional study was conducted within the framework of the Shiraz Heart Study (SHS) including 1982 adults. The validated 168 items food frequency questionnaire (FFQ) was used to assess participants’ dietary intakes. To investigate the association between LCDS and cardiometabolic risk factors, logistic regression, was conducted. Results During 5 years of follow-up, a total of 1982 adults, with a mean age of 53.07 ± 8.38 years, were included to the analysis. The adjusted model based on known confounding factors (age, sex, smoking, physical activity, energy intake and body mass index) revealed a significant decrease in a body shape index (ABSI) (OR = 0.70, 95% CI= (0.50 to 0.98), P = 0.038) comparing highest LCDS tertile vs. the reference. In contrast, risk of hypertension (HTN), body mass index (BMI), waist-hip ratio (WHR), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), atherogenic index of plasma (AIP), and fasting blood sugar (FBS) were not significantly associated with LCDS. Conclusion Current findings suggest that adherence to a low carbohydrate diet reduces ABSI, a main indicator of central obesity.